Design and analysis of terahertz oscillator for 6G systems - Zhou, Ziyao (Nanyang Technological University, 2024)
This dissertation investigates the utilization of the terahertz (THz) spectrum for forthcoming communication technologies, emphasizing the role of resonant tunneling diodes (RTDs) as crucial elements in terahertz communication architectures. It commences with a summary of the terahertz frequency domain, progressing to a detailed examination of the current-voltage (I-V) behavior of RTDs through the application of mathematical models and semiconductor physics principles. Furthermore, this document elaborates on the construction and deployment of RTD-driven terahertz emitters, integrated with sophisticated electromagnetic frameworks. Additionally, the thesis introduces an elaborate model for the communication mechanism leveraging RTD technology and assesses its efficacy, offering significant perspectives on the strengths and constraints of RTDs within the domain of terahertz communications.